HUBUNGAN KECANDUAN SMARTPHONE DENGAN KELUHAN NYERI MUSKULOSKELETAL PADA REMAJA - Dias Mitta Widianti, (2021)
Background: Various circles of society such as parents, teenagers, and children now almost all have smartphones. Smartphones have become a necessity ranging from personal, social, work, and even important in education. It can cause the use of smartphones, long duration in their use is called smartphone addiction has an impact on musculoskeletal complaints. Objective: To determine the relationship between smartphone addiction and complaints of musculoskeletal pain in adolescents. Method: Correlational descriptive with approach cross-sectional. The student population of Health Science Nutrition UPN Veterans Jakarta. With a sample size of 114. Instruments: Smartphone Addiction Scale, Nordic Musculoskeletal Questionnaire, and Numeric Rating Scale and then statistical tests, normality tests, and hypothesis testing. Data results: Spearman test Neck pain (P = 0.001), Shoulder pain (P = 0.000), Elbow pain (0.008), Wrist pain (P = 0.000), Upper back pain (P = 0.001), Lower back pain (P =0.004), hip pain (P= 0.202), knee pain (P=0.80), ankle pain (P=0.236). Conclusion: There is a significant relationship between smartphone addiction and complaints in musculoskeletal pain (neck pain, shoulder pain, wrist pain, upper back pain, lower back pain) in adolescents. However, there was no relationship between smartphone addiction and elbow pain, hip pain, knee pain, and ankle pain. Keywords: Smartphone, Musculoskeletal Pain, Adolescent